Local and landscape correlates of coccinellid species richness, abundance, and assemblage change along a rural–urban gradient in Quintana Roo, Mexico. (30th April 2022) - Catzim, Vannesa V.; Philpott, Stacy M.; Hénaut, Yann; García‐Arellano, Anmi; Pérez‐Lachaud, Gabriela
Abstract: Coccinellids are important predators and provide important ecosystem services. The coccinellid fauna, drivers of assemblage composition, and species richness in the tropics are poorly known. We studied changes in species composition of coccinellids in domestic gardens along a rural‐urban gradient in southeastern Mexico and identified the local and landscape variables that determine abundance and species richness. We surveyed coccinellids through monthly visual surveys, yellow sticky and pan traps in nine domestic gardens, and measured local variables (flower and prey abundance, plant diversity, garden size, temperature, and relative humidity), and gathered information on landscape heterogeneity in buffers around gardens (0.05 km, 1 km, and 3 km radius). We collected 40 coccinellid morphospecies, including two exotic species: Chilocorus nigrita and Delphastus catalinae . Coccinellid species composition differed along the gradient. Assemblages did not exhibit a nested pattern; species turnover was the main contributor of observed beta diversity. Overall coccinellid abundance was highest in the suburban zone, while overall species richness was highest in the rural zone. Mean abundance and mean species richness did not vary significantly along the gradient. The gradient negatively affected coccinellid diversity; diversity was highest in the rural zone which harbored several exclusive species. At the local scale, coccinellid abundance and species richness correlated positively with prey abundance and temperature, and negatively with plant diversity. Urbanization filtered more than half the species in the community, yet urban gardens in southeastern Quintana Roo, especially those providing abundant prey, might assist coccinellid conservation. Abstract in Spanish is available with online material Abstract : The drivers of coccinellid diversity in the tropics are poorly known. We studied changes in coccinellid assemblage composition, diversity, species richness, and abundance in domestic gardens along a rural to urban gradient in southeastern Mexico and identified variables that determine their species richness and abundance. Coccinellid assemblages varied significantly along the urbanization gradient, with more than half of the species filtered out of the urban zone. Only local variables were important drivers of coccinellid abundance and richness along the gradient. RESUMEN: Los coccinélidos depredadores brindan importantes servicios ecosistémicos. Los impulsores de cambios en sus ensambles y su riqueza de especies en los trópicos son poco conocidos. Nuestro objetivo fue identificar cambios en los ensamblajes de coccinélidos en 9 jardines domésticos a lo largo de un gradiente rural‐urbano en el sureste de México, e identificar variables locales y del paisaje que determinan su abundancia y riqueza de especies. Colectamos coccinélidos mensualmente y medimos variables locales (abundancia de flores y presas, diversidad de plantas, tamaño del jardín, temperatura, humedad relativa), y del paisaje en zonas de amortiguamiento alrededor de los jardines (0.05 km, 1 km y 3 km de radio). Recolectamos 40 morfoespecies, dos son especies exóticas: Chilocorus nigrita y Delphastus catalinae . La composición de especies de coccinélidos difirió a lo largo del gradiente. Los ensamblajes no exhibieron un patrón anidado, pero si un alto recambio de especies a lo largo del gradiente. La abundancia total de coccinélidos fue mayor en la zona suburbana, mientras que la riqueza total de especies fue mayor en la zona rural, sin embargo, los valores promedio no variaron significativamente. El gradiente afectó negativamente a la diversidad de coccinélidos. La abundancia de coccinélidos y la riqueza de especies correlacionaron positivamente con la abundancia de presas y la temperatura, y negativamente con la diversidad de plantas. Más de la mitad de especies de coccinélidos encontrados estuvieron ausentes de la zona urbana, sin embargo, los jardines urbanos que proporcionan presas abundantes, podrían ayudar a la conservación de los coccinélidos.